2002
DOI: 10.1080/02699050210131902
|View full text |Cite
|
Sign up to set email alerts
|

The development of awareness and the use of compensatory strategies for cognitive deficits

Abstract: In-depth qualitative exploration of the experiences of clients has the potential to provide guidance for more effective cognitive rehabilitation interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…However, the significant correlation between EF and metacognitive SA strongly suggests the importance of integrating an overall assessment of cognitive functions with a specific evaluation of self-awareness and of treating selfawareness contextually in a structured comprehensive rehabilitation program (Port et al, 2002). In fact, the inclusion of self-awareness in a multi-disciplinary rehabilitation program (Dirette, 2002) might enhance patients' self-awareness and participation in cognitive and functional tasks.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant correlation between EF and metacognitive SA strongly suggests the importance of integrating an overall assessment of cognitive functions with a specific evaluation of self-awareness and of treating selfawareness contextually in a structured comprehensive rehabilitation program (Port et al, 2002). In fact, the inclusion of self-awareness in a multi-disciplinary rehabilitation program (Dirette, 2002) might enhance patients' self-awareness and participation in cognitive and functional tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Whether they were attentive to their difficulties and able to identify errors in their actions also appeared to be conditions of great importance for many of the response actions. Dirette and others (16,44) have also emphasized that the ability of people with ABI to accurately recognize problems caused by the brain injury is linked to their ability to compensate. In addition, Ekstam et al (45) found that awareness of disabilities in people with stroke is related to their efficiency in the performance of tasks in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…For example, those with mild or severe impairments are less likely to compensate than those with moderate impairments, but people with pronounced amnesia but no other cognitive impairments are more likely to compensate than those with less pronounced amnesia and additional cognitive impairments (9). Awareness of deficits (16,19,20) and perceived self-efficacy (21) are also important for peoples' compensatory response actions. In addition, age, length of time postinjury and rehabilitation are likely to influence whether the compensatory response actions are successful or not (7,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that awareness of deficits, including the nature of psychosocial and physical problems, influences ones perception of their severity, the relationship between this and life satisfaction requires further exploration. Dirette (2002) explains that attaining awareness following TBI is a slow process that involves comparing performance on functional tasks in a familiar setting with their pre-morbid functional level. If participation in treatment raises awareness of problems previously not perceived as present by the individual, it is reasonable to presume a negative impact on life satisfaction despite functional treatment gain.…”
Section: Satisfaction With Lifementioning
confidence: 99%